Isu Gender dalam Al-Qur’an: Studi Penafsirsan Kontekstual Abdullah Saeed Terhadap Ayat-ayat Warisan - Afriadi Putra (Universitas Islam Negeri Imam Bonjol Padang, 2017)
There are not a few Muslims who make the story of Adam and Eve as an argument to consider women as a source of triggering sin.This study aims to find out the Qur'anic view of the story of the expulsion of Adam and Eve from heaven, expressing the comprehensive view of the Qur'an about the chronology of the exorcism of Adam and Eve and outlining the causes of the expulsion of Adam and Eve from Heaven. This study uses thematic method with Q.S. An-Nisa (4): 1 and al-A'raf (7): 22 as sources of data. Linguistic analysis was used to analyze the data. The results of the study showed that the emergence of this assumption is motivated by several reasons. Among the reasons is the history of Israiliyyat made by the classical interpreters as the primary source in interpreting the verses about Adam and Eve, which began at the end of the first century of Hhijriyah. The Israiliyyat narrations which speak of the story of Adam and Eve in general provide information which tends to make Eve a degrading party as well as a source of sin. This understanding ultimately affects the lowering of women's position over men in real life. In fact, if we examine directly the linguistic structure of the text of the verses in the Qur'an and read it holistically, and linked with the maqashid of equality of human creation, we will find that the Qur'an always makes Eve in an equal position with Adam.